Activation of germline-specific genes is required for limb regeneration in the Mexican axolotl - Zhu, Wei (2012)
The capacity for tissue and organ regeneration in humans is dwarfed by comparison to that of salamanders. Emerging evidence suggests that mechanisms learned from the early phase of salamander limb regeneration – wound healing, cellular dedifferentiation and blastemal formation – will reveal therapeutic approaches for tissue regeneration in humans. Here we describe a unique transcriptional fingerprint of regenerating limb tissue in the Mexican axolotl (Ambystoma mexicanum) that is indicative of cellular reprogramming of differentiated cells to a germline-like state. Two genes that are required for self-renewal of germ cells in mice and flies, Piwi-like 1 (PL1) and Piwi-like 2 (PL2), are expressed in limb blastemal cells, the basal layer keratinocytes and the thickened apical epithelial cap in the wound epidermis in the regenerating limb. Depletion of PL1 and PL2 by morpholino oligonucleotides decreased cell proliferation and increased cell death in the blastema leading to a significant retardation of regeneration. Examination of key molecules that are known to be required for limb development or regeneration further revealed that FGF8 is transcriptionally downregulated in the presence of the morpholino oligos, indicating PL1 and PL2 might participate in FGF signaling during limb regeneration. Given the requirement for FGF signaling in limb development and regeneration, the results suggest that PL1 and PL2 function to establish a unique germline-like state that is associated with successful regeneration.